Selection Criteria of Engineering-to-order Manufacturing Suppliers for Project Deliveries - Suomela, Juha-Pekka (My University, 2020)
This research studies the characteristics of the Engineer-to-Order (ETO) manufacturing and the selection criteria of the ETO manufacturing supplier. The main goal is to find relative importance of the four main criteria (quality, cost, time and flexibility) when selecting the ETO manufacturing supplier. This research studies also whether the background of the people has an effect to the criteria selection. The ETO manufacturing is by default project-based activity, where final delivery is based on the customer requirements and specification - therefore the nature and challenges of the projects are researched on the theory part together with the ETO manufacturer supplier selection criteria. There is a lot of relevant material available for project management and sourcing on general level, but less academic material can be found on this specific area of interest. The study highlights several challenges with the project deliveries; delivery scope changes, resource management, cost issues to name a few. To manage these challenges a structured project management approach is needed, and appropriate tools must be in place. This research is based on the nomothetical methodology with empirical approach and data is based on a survey done in the case company. The responders of the survey are known and have long working experience in the case company and are in contact with the ETO manufacturers directly or indirectly - therefore the data gathered is valuable and relevant. The response rate is relatively high (75%), indicating that the questions are relevant, and the survey was clear and understandable. The survey was done anonymously. The Case Company is a multi-national corporation with a several business units. The actual division, which this research was completed with, is manufacturing AC drives for different industries; HVAC, water & wastewater, process industry, food & beverage and marine to name a few. AC Drives are used for electric motor speed control and energy conversion and management, and the benefits of using drives are better process control and energy savings. Findings suggest that the four main criteria (quality, cost, time & flexibility) should not be equally weighted when selecting a supplier for ETO manufacturing; Quality and cost should have a higher importance, leading to a dilemma because these two criteria are somewhat contradictious. Background of the responders has a certain effect to the criteria selection; however, the differences are not statistically significant. Further study on this field is recommended.

Tämä lopputyö tutkii Engineer-to-Order (ETO) – valmistusta ja ulkoisen sopimusvalmistajan valintakriteerejä. Lopputyön tavoitteena on löytää neljän kategorian (laatu, kustannus, aika & joustavuus) keskinäinen suhde ulkoisen sopimusvalmistajan (Contract Partner) valintaa varten. Lisäksi tutkitaan, onko henkilöiden taustalla vaikutusta valintakriteereiden määrittelyyn. ETO valmistus on käytännössä aina projektitoimintaa, jossa lopputuote perustuu asiakkaan vaatimuksiin ja määrittelyihin. Tämän takia lopputyön teoriaosuudessa perehdytään projektitoimitusten ominaisuuksiin ja haasteisiin sekä sopimusvalmistajan valintaan. Tutkimusmateriaalia on hyvin saatavilla projektitoiminnasta ja ETO valmistuksesta yleisesti, mutta ETO valmistuksen ulkoistaminen on vähemmän tutkittu alue. Teoriaosuudessa huomataan, että pääasialliset haasteet projektitoimituksessa ovat projektin muutoksien hallinta, resurssien ohjausja projektin kustannuksien seuranta ja hallinnointi. Lisäksi projektitoimitusten menestyksellinen hoitaminen vaatii järjestelmällistä lähestymistapaa ja oikeita työkaluja. Tämä lopputyö perustuu nomoteettiseen tutkimusmetodiin, jossa käytetty data perustuu kohdeyhtiössä tehtyyn sisäiseen kyselyyn. Kyselyn kohderyhmänä on kohdeyhtiön omat työntekijät, jotka ovat tekemisissä ulkoisten ETO valmistajien kanssa säännöllisesti. Näin varmistetaan kerätyn materiaalin luotettavuus ja merkityksellisyys. Kysely tehtiin nimettömänä. Kyselyn vastausprosentti on erittäin hyvä (75 %) joten kyselyn kysymykset ovat merkityksellisiä, ymmärrettäviä ja hyvin muotoiltuja. Kohdeyhtiö on monikansallinen yritys, jolla on toimintoja eri teollisuuden sektoreilla. Tämä lopputyö tehtiin yrityksen Drives-segmentille, joka valmistaa taajusmuuttajia eri teollisuusaloille kuten kiinteistöt, merenkulku, energiateollisuus, vedenkäsittely ja prosessiteollisuus yleisesti. Taajuusmuuttajia käytetään oikosulkumoottorien nopeusohjaukseen, mutta myös etenevissä määrin energian hallintaan eri sovelluskohteissa. Taajuusmuuttajien käyttö parantaa prosessin hallintaa ja mahdollistaa energian säästön ja hallinnan. Lopputyön löydökset osoittavat, että toimittajan valinnan kriteerien (laatu, kustannus, aika & joustavuus) painotus ei ole tasainen; laatu ja kustannus nousevat selkeästi esiin tärkeimpinä valintakriteereinä. Tämä voi olla haaste, koska laatu ja kustannus ovat osittain vastakkaisia kriteerejä. Lisäksi vastaajien taustat vaikuttivat osittain kyselyjen tuloksiin, ei kuitenkaan tilastollisesti merkittävästi.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management